Tourism destination modelling: building a sustainable planning tool for Australian tourism destinations - Jones, Tod; Wood, David; Hughes, Michael; Pham, T.; Pambudi, D.; Spurr, R.; Dwyer, L.; Deery, M.; Fredline, L. (Sustainable Tourism CRC, 2010)
The Ningaloo Destination Model is a tourism planning tool for the Ningaloo Coast region of Western Australia that assesses the economic, social and environmental impacts of different planning decisions and events. This report describes the features of the tourism destination model, and analyses its application in the region and to other parts of Australia. Destination modelling integrates a number of research methodologies developed through past STCRC projects (on visitor spending and characteristics, social impacts and economic impacts), secondary data and ecological research. The key to this process is a model development technique that uses scenario planning methodologies to facilitate stakeholder engagement and conceptual modelling techniques to facilitate research integration. The report describes the methodologies used for model development and for data collection, provides two case studies demonstrating outputs, and explores applications of the Ningaloo Destination Model to the region, to other locations and to other sectors. The Ningaloo Destination Model provides estimates of the impacts of plans and events related to tourism in four dimensions: tourism specific; economy; social; and environmental (both resource use and ecological). These outputs are explored through two case studies: a nodal coastal development; and a large resort development. The model can be used for four broad (oftentimes overlapping) categories of assessment: operational planning and decision making for specific organisations and groups (such as local government or agencies that manage land or sea use), regional planning, participatory planning and collaborations and to assist monitoring and evaluation.The Ningaloo Destination Model will be available to the general public (in a limited format) through websites; to agencies through a desktop version; and through integration into a larger model of the region being developed by the CSIRO. Destination modelling is relevant for other tourism destinations and a process for the rapid and cost-effective application of destination modelling is feasible. While much of the data is available, a broader roll-out would require benchmarking of water, electricity and waste data, and developing a wireframe for all tourism destinations. Making destination modelling tools broadly available would significantly broaden the impacts considered in tourism planning and lead to enhancement of desirable effects of tourism development, and early mitigation of negative impacts across Australia. The techniques developed for destination modelling were also found to be applicable to other sectors.